Penerapan Model Discovery Learning untuk Meningkatkan Hasil Belajar Siswa Kelas V pada Mata Pelajaran Pendidikan Pancasila di Sekolah Dasar - Devi Dwi Oktavia; Tabroni Tabroni (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to improve student learning outcomes in Natural and Social Sciences (IPAS) through the application of the Discovery Learning model assisted by image media in grade V of Nurul Khoir Elementary School, Jambi City. This study is a classroom action research (CAR) conducted in two cycles, with each cycle consisting of planning, action, observation, and reflection stages. The subjects in this study were 26 fourth-grade students. Data collection techniques used included tests, observation, and documentation to obtain more comprehensive data on student learning outcomes. The results of the study showed an increase in student learning outcomes in each cycle. In cycle I, the percentage of student learning outcomes reached 73.92%, and increased in cycle II to 85.30%. This increase indicates that the application of the Discovery Learning model assisted by image media can improve student learning outcomes in the subject of IPAS. The Discovery Learning model provides opportunities for students to learn actively and independently, by utilizing attractive image media and making it easier for students to understand the concepts taught. Thus, this model can be used as an alternative in a more effective and interesting learning process. Furthermore, the implementation of this model also had a positive impact on student engagement in learning activities, making the teaching and learning process more interactive and enjoyable. This study recommends that the Discovery Learning model, assisted by image media, be applied more widely across various subjects to improve the quality of learning in elementary schools. In the future, this research can also be continued by examining the application of similar models in other subjects and measuring their impact on improving students' cognitive abilities and overall skills.